2011
DOI: 10.1096/fj.11-185207
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protocadherin‐1 expression in primary bronchial epithelial cells: association with epithelial cell differentiation

Abstract: Protocadherin-1 (PCDH1) is a novel susceptibility gene for asthma that is expressed in airway epithelium. We aimed to characterize PCDH1 mRNA transcripts and protein expression in primary bronchial epithelial cells and to determine regulation of PCDH1 during mucociliary differentiation. Total RNA and protein were isolated from human primary bronchial epithelial cells. PCDH1 transcripts were characterized by rapid amplification of cDNA ends in bronchial epithelial cells of 4 subjects. PCDH1 expression was quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 45 publications
0
54
0
Order By: Relevance
“…PCDH1 belongs to a large group of cell-cell adhesion molecules. It is expressed in several tissues, including airway epithelium and skin keratinocytes [10,11]. It shows intracellular signalling abilities, is thought to play a role in cell repair and is expressed during fetal lung development in mice [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…PCDH1 belongs to a large group of cell-cell adhesion molecules. It is expressed in several tissues, including airway epithelium and skin keratinocytes [10,11]. It shows intracellular signalling abilities, is thought to play a role in cell repair and is expressed during fetal lung development in mice [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in delta-pcdhs genes may be responsible for the pathogenesis of several neurological disorders and carcinogenesis. For instance, Koppelman et al (2009) found that pcdh1 was a susceptibility gene for bronchial hyperresponsiveness, and Koning et al (2012) found that pcdh1 was a novel susceptibility gene for asthma that is expressed in airway epithelium. Philibert et al (2012) found that the deficiency of pcdh12 led to modifications in the structure and function of arteries.…”
Section: Introductionmentioning
confidence: 99%
“…The three-exon isoform does not encode the cytoplasmic domains CM1-3 that are present in the five-exon isoform. Recently, a sixth exon and alternative expression of exon 1 were identified in bronchial epithelial cells [11], whereas skin epithelial expression of PCDH1 has not been extensively characterised to date.…”
mentioning
confidence: 99%
“…So far, no data are available on the functional effects of any of the asthma-and eczema-associated SNPs. Finally, adding to the complexity of PCDH1, its expression is also probably regulated by epigenetic mechanisms that include gene methylation, given the identification of exon 1A as a CpG island that is potentially methylated [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation